Kombinasi Berat Beban dan Lama Pengepresan pada Pembuatan Keju Lunak Rampelas (Ficus ampelas) dengan Koagulan Alami Pengganti Rennet - Sugitha, I Made; Puspawati, Ni Nyoman; Wiadnyani, AAI. Sri (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2017)
This aims of the research to obtain coagulant alternative materials as rennet replacement ,which until now its has still a great price and should to import for manufacturing process ofsoft cheese . The long-term goal of this research is to produce a good cheese qualityproduction by using a natural coagulant of babakan rampelas (Ficus ampelas) as rennetsubstitute has a price cheaper than the natural cheese processing product .. The specificpurpose of this research is to know the optimum pressing time and the heavy burden forproducing soft cheese product that combined with lactic acid bacteria in the proceses. Thisstudy used a Randomized Complete Design with time as a treatment consists of 4 levels,namely 12, 14, 16 and 18 hours and heavy pressing load l which consists of 3 levels i.e. 1 kg,1.5 kg and 2 kg. The treatment repeated as many as 3 times so that the retrieved 36 unitexperiment. The observed parameters include: Rendement, water, protein, fat, Lactic acidbacteria and sensory evaluation test. The conclution of the research that 16 hr and 2 kgloading weight of the best treatment were efected to rendement,(54.57%,; water( 64,22%);ash( 0,94%); protein(14,16%), fat(24,27%); and LAB content(5.0330 log cfu/g of soft cheseproduct.
Keywords: soft cheese; babakan rampelas ( ficus ampelas); rennet